Comparative evaluation of Ordered Subset Expectation Maximization and Bayesian Penalized Likelihood algorithms for PET/CT image reconstruction in various malignancies using 18F-FDG and 68Ga-PSMA-11 tracers - Naeimi, Arvin; Harsini, Sara; Aghdam, Ramin Akbarian; Klein, Ran; Abbaspour, Farzad (Frontiers in Oncology, 2025)
PurposeThis study compares the Ordered Subset Expectation Maximization (OSEM) and Bayesian Penalized Likelihood (BPL) algorithms for Positron Emission Tomography/Computed Tomography (PET/CT) image reconstruction using 18F- fluorodeoxyglucose (FDG) and 68Ga-labeled Prostate-Specific Membrane Antigen(68Ga-PSMA-11) tracers.MethodsA retrospective analysis was conducted on 33 patients with various malignancies, including 25 undergoing 18F-FDG PET/CT scans and 8 undergoing 68Ga-PSMA-11 PET/CT scans. Scans were reconstructed using both OSEM and BPL (Q.Clear) algorithms, evaluating key metrics such as Standardized Uptake Value (SUV)max, SUVpeak, background SUV, and tumor-to-background ratio (TBR).ResultsThirty-three patients (mean age: 67.53 ± 11.78 years) with 100 lesions (80 FDG, 20 PSMA) were analyzed. In the FDG group, significant differences were observed in lesion SUVpeak, liver SUVpeak, SD of liver SUVmean, bladder SUVmean, SD of bladder SUVmean, and TBR, with BPL generally producing higher values except for liver SUVpeak, SD of liver SUVmean, and SD of bladder SUVmean. In the PSMA group, BPL enhanced most metrics except for the SD of liver SUVmean and the SD of bladder SUVmean. While strong linear correlations between BPL and OSEM metrics were observed (Pearson r>0.85 for most parameters), Bland-Altman analysis revealed wide limits of agreement, particularly for TBR in the PSMA group (-13.00 to 23.89), indicating substantial variability in absolute values between methods. Assessment of the relationship between lesion volume and SUVmax differences (BPL–OSEM) revealed a weak, non-significant negative correlation in the total cohort(r = – 0.14, p = 0.16) and in the FDG subgroup(r= – 0.14, p = 0.24).ConclusionBoth reconstruction methods demonstrate clinical utility, with BPL producing statistically higher values for several quantitative metrics, such as SUVmax and TBR, without markedly improving lesion detectability. While strong correlations were observed between BPL and OSEM values, the wide limits of agreement, particularly for TBR in PSMA imaging, suggest these methods may not be directly interchangeable in longitudinal studies. Harmonization strategies may help reduce inter-method variability and improve scan comparability in longitudinal or multicenter settings. Prospective approaches, such as reconstruction-specific reference ranges or scaling factors, could further support harmonization efforts in clinical trials. For longitudinal monitoring, consistent use of the same reconstruction method is recommended to ensure reliable quantification.